Time Series Modeling Of International Tourists Arrivals In Malaysia For Prediction And SME Business Planning - Jayaraman, Krishnaswamy; Lin, Soh Keng (Universiti Sains Malaysia, 2011)
The time series models have been constructed to predict the number of international arrivals into Penang by air and sea based on the avai lable data from January 2002 to December 2007. The month-wise seasonal factor has been determined and consequently the peak, moderate and lean tourists months have been detected.